FAKTOR – FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Inez Cornelia Risamasu; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to examine the factors that influenced going concern audit opinion. This research was in the form of quantitative, in which the data obtained from Indonesia Stock Exchange and bloomberg. The sample used in this research was 49 manufacturing companies listed on Indonesia Stock Exchange 2011 – 2015 then the data processed by using software SPSS Version 23. Data analysis technique used was logistic regression analysis. The results showed the debt default had no affect on the provision of going concern audit opinion, firm size had no affect on the provision of going concern audit opinion, the previous year's audit opinion had a significant positive effect on the provision of going concern audit opinion, financial condition had a significant negative affect on the provision of going concern audit opinion, company size had no affect the provision of going concern audit opinion.